CONSOLIDATING PARTICIPATORY DEMOCRACY IN AFRICA: THE CHALLENGES AND THE WAY FORWARD - Adegboye, A. A. (European Scientific Journal, ESJ, 2013)
Pro-democracy reforms hit Africa like a tidal wave in the 1990s, sweeping away authoritarian regimes and the one – party system that had dominated the African scene since independence. This began with the 1988 riots in Algiers, the 1990 release of Nelson Mandela after twenty – seven years in South Africa’s prisons and the crisis that followed the annulment of June 12, 1993 presidential election in Nigeria. For the most part, changes came about because both military and civilian governments had failed to alleviate poverty, unemployment, and oppression and had not provided their citizens with such basic services as health, housing, and education. Administrative inefficiency, political corruption, economic mismanagement and social decay had further undermined the authority of authocratic leaders and national institutions. These unpalatable conditions led to popular demands for reform throughout Africa. This paper examines the various challenges facing democracy in Africa and proposes solutions intended to give democracy a chance to flourish in African counties.